2015
DOI: 10.1016/j.exer.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The rat retina has five types of ganglion-cell photoreceptors

Abstract: Intrinsically photosensitive retinal ganglion cells (ipRGCs) are inner retinal photoreceptors that mediate non-image-forming visual functions, e.g. pupillary constriction, regulation of pineal melatonin release, and circadian photoentrainment. Five types of ipRGCs were recently discovered in mouse, but whether they exist in other mammals remained unknown. We report that the rat also has five types of ipRGCs, whose morphologies match those of mouse ipRGCs; this is the first demonstration of all five cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 73 publications
2
79
0
Order By: Relevance
“…33 46,59 Studies in the rat have also confirmed the existences of at least five subtypes of pRGCs, with anatomical and biophysical properties similar to murine pRGCs, albeit with a slightly greater diversity of light responses observed between M2-and M5-type cells. 59 It is also worth noting that at least two distinct populations of pRGC have also been described in the primate retina with similarities to M1-and non-M1-type pRGCs. 51,60,61 However, to date, the functional properties of these cell types has not been investigated in detail.…”
Section: Correlation Of Prgc Subtypes With Response Typesmentioning
confidence: 83%
See 1 more Smart Citation
“…33 46,59 Studies in the rat have also confirmed the existences of at least five subtypes of pRGCs, with anatomical and biophysical properties similar to murine pRGCs, albeit with a slightly greater diversity of light responses observed between M2-and M5-type cells. 59 It is also worth noting that at least two distinct populations of pRGC have also been described in the primate retina with similarities to M1-and non-M1-type pRGCs. 51,60,61 However, to date, the functional properties of these cell types has not been investigated in detail.…”
Section: Correlation Of Prgc Subtypes With Response Typesmentioning
confidence: 83%
“…Despite their significantly larger photocurrents, it is worth noting that M1-type pRGCs exhibit maximal action potential spike firing rates that are notably lower than those of M2, M3, M4, and M5-type pRGCs, 46,59 an observation that is potentially explained by the increased propensity of M1 cells to attain a state of depolarisation block during light responses. 33 46,59 Studies in the rat have also confirmed the existences of at least five subtypes of pRGCs, with anatomical and biophysical properties similar to murine pRGCs, albeit with a slightly greater diversity of light responses observed between M2-and M5-type cells.…”
Section: Correlation Of Prgc Subtypes With Response Typesmentioning
confidence: 95%
“…The procedures for euthanasia, eyecup generation, whole-cell recording and light stimulation have been described in a recent publication (Reifler et al, 2015). To summarize, a rat was dark-adapted the night before each experiment beginning around 6 PM.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, melatonin could modulate ipRGCs by acting either directly on them or on their presynaptic circuits, or both. Here, we tested this hypothesis by focusing on the alpha-like M4-type ipRGCs, whose unusually large somas enable them to be identified for whole-cell recording with relative ease (Estevez et al, 2012, Schmidt et al, 2014, Reifler et al, 2015), thereby obviating the need for fluorescent labelling (Berson et al, 2002, Ecker et al, 2010). We studied the effects of exogenous and endogenous melatonin on M4 cells’ resting membrane potential, spontaneous spike rate, rod/cone-driven (“extrinsic”) light responses, and melanopsin-mediated (“intrinsic”) light responses.…”
mentioning
confidence: 99%
“…Two types of primate ipRGCs have been recorded and both exhibited robust rod-driven light responses (Dacey et al, 2005), but five ipRGC types have since been discovered in rodents, of which only the M1 type innervates the SCN (Ecker et al, 2010). We learned recently that while mouse M1 cells display rod-driven photoresponses as robust as those of primate ipRGCs (Zhao et al, 2014), rat M1 cells’ rod/cone-mediated responses are far weaker (Reifler et al, 2015). The SCN-projecting ipRGCs in primates could resemble those in rats.…”
mentioning
confidence: 99%